Seismic retrofitting of existing RC buildings: a rational selection procedure based on Genetic Algorithms. (December 2019) - Falcone, Roberto; Carrabs, Francesco; Cerulli, Raffaele; Lima, Carmine; Martinelli, Enzo
Abstract: Reinforced Concrete (RC) structures built in the past decades in earthquake-prone regions do not generally meet the seismic safety standards requested by the current codes. Therefore, they generally need to be retrofitted with the aim to reduce their seismic vulnerability within acceptably low levels. Although several technical solutions are nowadays available on the market, the design of retrofitting interventions is mainly based on the so-called "engineering judgment" and, hence, it is highly subjective in nature, yet being bound to respecting strict code provisions. This paper proposes a rational procedure, based on the application of Genetic Algorithms (GAs), intended at selecting the "cheapest" retrofitting solution among the technically feasible ones. The paper shows how the main GA operators (namely, selection, crossover, and mutation) operate on the candidate retrofitting solutions, which, in principle, may consist of a combination of both member- and structure-level techniques. Details about the numerical implementation of the proposed procedure are reported, along with the summary of some relevant applications to RC frames representative of a wide class of buildings currently existing in South European Countries, such as Italy and Greece.